Efficacy of Synthetic Insecticides against Barley Shoot Fly (Delia Arambourgi) in Barley cultivation in the Central Highlands of North Shewa, Ethiopia - Fekadu Tewolde; Muluken Goftishu (Universitas Andalas, 2025)
Barley Shoot Fly (BSF) Delia Arambourgi Seguy causes tremendous yield loss in barley. Five foliar and two seed dressing insecticides were evaluated on variety HB-1307 against shoot fly at Debre Birhan Agricultural Research Center DBARC and Ankober station in 2021, the primary cropping season. The experiment aimed to select an effective and economical insecticide for barley shoot fly. Randomized Complete Block Design with three replications was used for the study, and data were analyzed using R software with a generalized linear mixed-effect model. Treatment means were separated using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Seed dressing insecticides were applied on barley seed immediately before planting, and insecticides were used according to factory recommendations. Combined result showed that from foliar insecticides lambda cyhalothrin 5% EC, from seed dressing insecticides Thiamethoxam 25% WG were effective in decreasing the number of larvae and dead heart shoots, and gave maximum marginal rate of return and higher net benefit than the rest of the treatments. Therefore, we recommend proper use of Lambda cyhalothrin 5% EC at a rate of 0.25 lt/ha using 200 L water/ha and 4 g Thiamethoxam 25%WG 1/kg seed dissolved in 600 ml water for effective management of barley shoot fly. Based on this finding, examining sowing date and seed dressing insecticides in future research may provide yield increments in barley.